In bloom - Michaels, Fern; Foster, Lori; Brown, Carolyn (Zebra Books, 2022)
Amazing Grace - After years spent traveling the world as a flight attendant, Gracie Walden is ready to stay a little closer to her roots, starting with two weeks at home in Amarillo, Texas. But there's unexpected turbulence between her mother, Ella, and her older sister, Hope - and it will lead to a revelation that changes Gracie's life in amazing ways...